Vivencia relacional y reparación psicológica de los niños institucionalizados (2014)
ABSTRACT: This paper presents the results of the research “Establishment of the repairing link among deprived children and the institutions of social protection”, which makes emphasis on two dimensional concepts: a first point of analysis referring to the relational dynamics of children, and a second one that analyzes the psychological repair in the context of institutionalization. Methodology: the research was directed from a qualitative methodological approach. Semi-structured interviews and the application of projective tests were carried out. Participants included 20 children and adolescents who experienced a loss situation in the early childhood and the team of caregivers of two child protection institutions. Conclusions: it was found that, although the caregivers of children serve as emotional containers in their institutions, the repair of the relational system requires a specific figure with whom the child could reactivate the good aspects of the internal object.